PENGARUH PENDEKATAN VALUE CLARIFICATION TECHNIQUE (VCT) METODE PERCONTOHAN TERHADAP HASIL BELAJAR PKn SISWA SD - Sari Nst, Diana Novita; Reinita, Reinita; Mansur, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of  Value Clarification Technique (VCT) modeling method on the studnts’ learning outcome in civic education. This study is a quasi-experimental design with a non-equivalent control group. The research was conducted in elementary school Number 13 Cingkariang Banuhampu Sub-district of Agam District with class VA as the experimental class and Class VB as the control class. Both classes have twenty five students. The data analysis technique employed was the normality test and homogeneity test, which was then followed by a t-test to see the effect of VCT. The results show that the average pretest score is 38,768 for the experimental class and 41,488 for the control class. The average posstest score is 90,68 for the experimental class and 86,32 for the control class. The result of the t-test shows that the tcount is 1,73 and the ttable on the significance level of 0,05 is 1,6772, which means that tcount>ttable. Therefore, it is concluded that the Value Clarification Technique modeling method affects the students’ learning outcome in civic education in Elementary School Number 13 Cingkariang.  Keyword : The Value Clarification Technique (VCT) Modeling Method, Students’  Learning Outcome, Civic Education.